ادارة الوقت وأثرها في تحسين الانتاجية : في الشركة العامة لصناعة الادوية و المستلزمات الطبية في نينوى - د. صباح انور يعقوب; خالدة عثمان محمود (PROSPECTIVE RESEARCHES, 2023)
Time Management is considered as one of the concepts which have been focused on recently for it includes the concept of time which plays avital role in human life and in the progress of companies’ wether industrial or service via organizing production operation time and saving unuitilized times. This research focuses on identifying the time concept, importance, management, and management stages, also the meaning and importance of productivity and its improvement methods in the state company for drugs industry and medical appliances in Nineveh by collecting the opinion of (70) employees at the (upper, middle, and lower) levels. The research comes up with many results. The most important one that there is significant relationship and effect between time management and productivity improvement, the research present a number of recommendations, the most important one that there must be a time management unit or department at the company under research helps in recording, analyzing and organizing the times of work and production to improve the productivity of the company